Baseline autonomic nervous system activity in female children and adolescents with conduct disorder: psychophysiological findings from the FemNAT-CD study - Oldenhof, Helena; Kieser, Meinhard (Journal of criminal justice, 2019)
Purpose - Autonomic nervous system (ANS) functioning has been widely studied in relation to antisocial behavior, such as Conduct Disorder (CD). However, research in females is scarce and findings are inconsistent. This study investigated baseline ANS activity in CD children and adolescents and tested for sex differences. Furthermore, subgroups of CD were investigated: +/‐ Limited Prosocial Emotions (LPE), +/‐ comorbid internalizing disorders (INT). - Methods - Baseline ANS activity was measured by Heart Rate (HR), Heart Rate Variability (HRV; parasympathetic activity), Pre-Ejection Period (PEP; sympathetic activity), and Respiration Rate (RR). 659 females (296 CD, 363 controls) and 351 males (187 CD, 164 controls), aged 9-18years participated. - Results - Baseline HR, HRV and PEP did not differ between CD subjects and controls in both sexes. RR was higher in CD participants than controls amongst females, but not males. LPE was unrelated to ANS activity, whereas females with CD+INT presented lower HRV. - Conclusions - These results suggest that baseline ANS activity is not a robust indicator for CD. However, deviant ANS activity - especially parasympathetic activity - was observed in CD females with internalizing comorbidity. The psychophysiological abnormalities observed in this subgroup are indicative of emotion regulation problems. Accordingly, this subgroup may require specific interventions.